Inspirations from Laudato Si’ for Landscape Architecture Design in Cities - Jakubowski, Kasper (Studia Ecologiae et Bioethicae, 2017)
This paper presents an original study on the encyclical Laudato Si’ (LS) in the context of environmental problems of modern cities and contemporary landscape architecture. The Holy Father’s encyclical provides an inspiring diagnosis and description of the contemporary phenomena which draws on the achievements and findings of various fields of research. In the paper, the author formulates ten themes based on LS in the light of cities’ sustainable development and landscape architecture design. The Pope points out the interdependence between the natural environment and society. A detailed analysis shows that the overtone of the conclusions contained in the document is rather positive: there are other possible scenarios for the urban development and new standards for shaping (or, where necessary, restoring) the urban environment. The author analyses proposals of changes and practical solutions providing inspiration for the social, environmental, and spatial renewal of modern cities. The author analyses them in the context of contemporary achievements in landscape architecture where one of the most important prospects and future topics is urban landscape restoration.